Physical Principles of Electron Microscopy : An Introduction to TEM, SEM, and AEM - Egerton, R.F (New York, NY : Springer Berlin Heidelberg, 2016)
This popular textbook provides an introduction to the theory and practice of electron microscopy. The second edition has been updated to reflect the recent developments, including correction of lens aberrations in a TEM column and new material on environmental TEM and SEM. The text is linked to a new website that contains additional educational material such as sample exam questions and answers to selected problems. This edition also contains expanded reference lists that allow the reader to efficiently explore key topics in greater depth. Scanning and fixed-beam electron microscopes are an indispensable tool for both research and routine evaluation in the physical, biological and medical sciences, including specialized fields in materials science, nanotechnology and semiconductor processing. Physical Principles of Electron Microscopy, Second Edition, is ideal for students, researchers, and technologists who make use of electron microscopes but have only a limited knowledge of physics and mathematics. Undergraduate students will understand how basic principles of physics are utilized in this important area of applied science, while university teachers and researchers will find a concise but authoritative teaching, supplemental, or reference text covering the basic principles and practice of microscopy.
n Introduction to Microscopy -- Electron Optics -- The Transmission Electron Microscope -- TEM Specimens and Images -- The Scanning Electron Microscope -- Analytical Electron Microscopy -- Special Topics -- Appendix: Mathematical Derivations.
(3ebQQGJ OQGSjI dWdGH GdLGeYI (B2024.s
Keywords: Materials science; Nanotechnology; Microscopy; Spectroscopy